2021
DOI: 10.3390/ijerph18084012
|View full text |Cite
|
Sign up to set email alerts
|

Are Clean Technologies More Effective Than End-of-Pipe Technologies? Evidence from Chinese Manufacturing

Abstract: An increasing number of manufacturing enterprises are adopting environmental technologies to cope with the increasingly severe environmental regulatory pressure, but the existing studies about the impact of environmental technologies on economic performance come up with mixed results. This paper contributes to the literature by using the financial constraints and market advantages as a dual mediating process in this relationship. An empirical test using a sample of Chinese manufacturing enterprises listed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Kuntluru et al (2008) and Tanaka (2021) explored a positive relationship between AGE and the firm's performance. On the contrary, the studies by Park et al (2010); Charoenrat and Harvie (2013); Li et al (2021);and Faruq et al (2023) found a negative relationship between the variables.…”
Section: Control Variablesmentioning
confidence: 81%
See 1 more Smart Citation
“…Kuntluru et al (2008) and Tanaka (2021) explored a positive relationship between AGE and the firm's performance. On the contrary, the studies by Park et al (2010); Charoenrat and Harvie (2013); Li et al (2021);and Faruq et al (2023) found a negative relationship between the variables.…”
Section: Control Variablesmentioning
confidence: 81%
“…Prior studies revealed that large firms enjoy economies of scale, relatively lower adjustment costs, and easy access to the credit markets (Chandrapala and Knápková, 2013;Tanaka, 2021). A number of scholars, such as Li et al (2021); Khan et al (2018); and Molodchik et al (2016), examined the positive impact of SIZE on firm performance. Conversely, Masnoon and Saeed (2014); Ullah et al (2017); Tran and Vo (2020); and Ullah et al (2020) reported the opposite relationship between both variables.…”
Section: Control Variablesmentioning
confidence: 99%